Perancangan Tata Letak Gudang pada Distributor Unicharm Menggunakan Metode Class Based Storage - Ismiyah, Aizzatul; Eka Dewy Karunia Wati, Putu (SURYA TEKNIKA, 2024)
The warehouse system is the most important part of the Company. Good conditions and arrangements will reduce losses to the Company, minimize rental costs, and speed up warehouse operations. The warehouse must have a model that can simplify and speed up the process of searching for goods. This problem occurred at the Unicharm distributor, because there was no definite arrangement, which resulted in products that did not match the category and stockpiling that was too high. This results in damaged goods and long searches. Seeing this problem, it is necessary to design and reorganize the existing storage warehouse. In this problem, the Class Based Storage method is used combined with ABC Classification. The results obtained from this proposed layout are time and distance efficiency of 24.82%.